ESTIMASI KEDATANGAN PELANGGAN DAN TRANSAKSI PESANAN RUMAH MAKAN MAHIRA MENGGUNAKAN RENEWAL-REWARD PROCESS - AMBARITA, PIONITA MARETTI BR; SEKARINI, KETUT GITA; PASARIBU, TASSYA MURNI; TAMBUN, WIRA PRANATA T.; OCTAVANNY, MADE AYU DWI (E-Jurnal Matematika, 2026)
Random fluctuations in customer arrivals at restaurants often result in suboptimal operational planning based on subjective estimates. This study aims to estimate customer arrival patterns and transaction values at Mahira Jimbaran Restaurant using the renewal-reward process approach, as well as to calculate long-term revenue rates. The methods used include collecting primary data for 4 hours on Saturday, November 8, 2025 (1:00 p.m. to 5:00 p.m. Wita) by recording the time between arrivals and the transaction value per customer. The analysis was conducted by calculating the expected transaction value (E[R]), expected inter-arrival time (E[X]), and long-term reward rate using the Wald Equation. The results show an average transaction of IDR 23,808.99 per customer, an average inter-arrival time of 2.013 minutes, and a revenue rate of IDR 11,828.67 per minute. These quantitative estimates can be used as a basis for operational decision-making related to workforce scheduling, queue management, and raw material planning.